PERANAN GURU PPKn DALAM MENERAPKAN DISIPLIN SISWA KELAS X SMA NEGERI 6 PONTIANAK - Umi Listari; Sulistyarini Sulistyarini; Thomy Sastra Atmadja (Universitas Tanjungpura, 2019)
Abstract The method used in this research is descriptive research method with the form of research used in qualitative research. The subjects of this study were the X grade students of SMA Negeri 6 Pontianak. The data collection techniques used in this study were direct communication techniques, observation. The results of the research were: 1) The role of the PPKn teacher in time discipline in class X SMA Negeri 6 Pontianak violated by students that is coming late, in and out of class, clothes are removed this is the most common violation of X students in SMA Negeri 6 Pontianak. 2) The role of the PPKn teacher in the discipline of enforcing the rules in class X of SMA Negeri 6 Pontianak is very good, this can be seen from the assertiveness of the teacher in enforcing existing rules or regulations to students who commit violations. 3) The role of the teacher in applying discipline to overcome attitudes Class X students at SMA Negeri 6 Pontianak, very good, this can be seen from the assertiveness of teachers in enforcing the rules or regulations that exist to students who commit violations. Keyword : The Role of Teachers, PPKn, Discipline.